Implementasi Penyelenggaraan Program Pendidikan Profesi Guru (PPG) Pendidikan Agama Islam di LPTK UIN Serang Banten - Farida Hanun (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
Abstract Research on the Implementation of Teacher Professional Education for Islamic Religious Education Teachers at UIN Sultan Maulana Hasanuddin Serang Banten aims to find out the implementation of the Teacher Certification Program through PPG in position for GPAI with a qualitative method. The results of the study concluded that: (a) the PPG program has a very large role in improving the quality of PAI teachers, (b). The input component has been well proven by the readiness of participants, quality of lecturers, facilities and infrastructure that support the PPG program, c ) . Components of the learning process of the online learning system (online) and face to face directly through workshops, Peer Teaching, and PPL. Everything went well, although not optimally, (d). The output component of the PPG implementation was from 90 students that had participated in the PPL it was recorded that 100% of students passed the performance test. Meanwhile, in the knowledge test 58 participants (64%) passed and 32 people (36%) Â Abstrak Penelitian Implementasi Penyelenggaraan Pendidikan Profesi Guru bagi Guru Pendidikan Agama Islam di UIN Sultan Maulana Hasanuddin Serang Banten bertujuan mengetahui untuk mengetahui implementsi penyelenggaraan Program Sertifikasi Guru melalui PPG dalam jabatan bagi GPAI dengan metode kualitatip. Hasil penelitian menyimpulkan bahwa: (a) Program PPG sangat besar peranannya terhadap peningkatan kualitas guru PAI, (b) Komponen input sudah baik terbukti dengan kesiapan peserta, kualitas dosen, sarana dan prasarana yang mendukung program PPG, (c) Komponen proses pembelajaran melalui sistem pembelajaran Daring (online) dan tatap muka secara langsung melalui loka karya, Peer Teaching, dan PPL. Semua berjalan dengan baik meskipun belum maksimal, d) Komponen output dari penyelenggaraan PPG adalah dari 90 mahasiswa yang telah mengikuti PPL, tercatat 100 % mahasiswa lulus dalam uji kinerja. Sedangkan pada ujian pengetahuan peserta yang lulus adalah 58 orang (64%) dan yang tidak lulus atau harus mengulang sebanyak 32 orang (36%).